Patriotism, Cosmopolitanism, Consumer Ethnocentrism and Purchase Behavior in Kazakhstan - Rybina, Liza; Reardon, James; Humphrey, Janet (Organizations and Markets in Emerging Economies, 2010)
The purpose of this research is to analyze the influence of consumer ethnocentrism and its antecedents - patriotism and cosmopolitanism on consumer domestic and foreign buying behavior in the emerging economy of Kazakhstan. This country poses an interesting question as to how the effects of attitudes and purchase behavior differ in the once controlled regime after receiving independence from a dominant regime. These different attitudes likely affect international integration of Kazakhstan into the global economy. As expected, consumer ethnocentrism leads to high consumption of domestically produced goods and to the lower level of consumption of imported products. Patriotism has a significant positive effect and cosmopolitanism has a significant negative effect on ethnocentric attitudes of consumers in the country studied. The findings of the present study suggest that Kazakhstan seems to have a strong negative link of cosmopolitanism on ethnocentric attitudes and overall, this country seems to have the promise of becoming integrated into the global economy. Managerial implications of the findings are considered and directions for the future research are identified.